Long‐term symptoms of polyneuropathy in breast and colorectal cancer patients treated with and without adjuvant chemotherapy. (29th May 2020) - Bennedsgaard, Kristine; Ventzel, Lise; Themistocleous, Andreas C.; Bennett, David L.; Jensen, Anders B.; Jensen, Anni R.; Andersen, Niels T.; Jensen, Troels S.; Tankisi, Hatice; Finnerup, Nanna B.
Abstract: Background: The aim of this study was to assess chemotherapy‐induced polyneuropathy (CIPN) 5 years after adjuvant chemotherapy in patients with breast and colorectal cancer. The association of CIPN with quality of life, anxiety, and depression was analyzed. Methods: Of a set of 100 patients with breast cancer and of 74 with colorectal cancer who had undergone surgery and adjuvant chemotherapy in 2011‐2012, 80 and 52 patients alive, respectively, were included together with two reference groups of 249 breast cancer patients and 83 colorectal cancer patients who had undergone surgery only. All patients were sent a questionnaire on alcohol consumption, smoking habits, comorbidity, medicine consumption, and oxaliplatin‐specific questions, as well as the Michigan Neuropathy Screening Instrument questionnaire (MNSIq), the Douleur Neuropathique 4 Questions (DN4q), the EQ‐5D, and the Hospital Anxiety and Depression Scale. Possible polyneuropathy was defined as the presence of numbness and/or tingling in the feet, secondly as a score of ≥4 on the MNSIq. Possible painful polyneuropathy was defined as pain in both feet and a score ≥3 on the DN4q. Results: The prevalence of possible polyneuropathy defined by numbness and/or tingling in the feet was 38.8% (28.1‐50.3) after adjuvant docetaxel and 57.7% (43.2‐71.3) after adjuvant oxaliplatin, with no significant difference from a previous 1‐year follow‐up ( P >.35). Fewer had possible polyneuropathy as defined by the MNSIq. Patients with possible polyneuropathy after adjuvant chemotherapy reported significantly lower quality of life than patients treated with surgery only. Conclusion: Symptoms of polyneuropathy following adjuvant docetaxel and oxaliplatin persist 5 years after treatment and affect quality of life negatively. Abstract : Symptoms of polyneuropathy after adjuvant chemotherapy persist after 1 year. Patient with neuropathy has a lower quality of life